PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA GURU SDN KOTA BARU III - Aida Fahriyah; Nuridin (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
To determine the effect of leadership and motivation on teachers’s work performance in the Kota Baru III Elementary School. The purpose of this research is included in the category of causal associative research using a quantitative approach. The research was conducted by distributing questionnaires to respondents, all of whom are teachers of the Kota Baru III Elementary School, while the research method uses simultaneous and partially linear regression analysis. The hypothesis states that leadership and motivation simultaneous have a positive effect on work performance. The hypothesis that partially states that leadership and motivation affect teachers work performance in Kota Baru III Eelementary School.